International survey on diagnosis and management of hypotension in extremely preterm babies - Stranak, Zbynek; Semberova, Jana; Barrington, Keith; O'Donnell, Colm; Marlow, Neil; Naulaers, Gunnar; Dempsey, Eugene; HIP consortium (European journal of pediatrics, 2014)
UNLABELLED: Hypotension is a commonly diagnosed and treated complication of extremely low gestational age newborns (ELGAN), but enormous variation in diagnosis, management and clinical practice has been documented. We sought to evaluate practice regarding the management of hypotension in ELGANs and developed a web-based questionnaire addressing diagnosis, intervention thresholds and modes of treatment of hypotension in ELGANs. We received 216 completed questionnaires from respondents in 38 countries. Most responses (83 %) were from specialist units where, together, over 26,000 very low birth weight (VLBW) infants are cared for annually. The majority (73 %) defined hypotension as a mean blood pressure (BP) in mmHg less than the gestational age in weeks. Sixty percent assessed the circulation with additional methods; echocardiography was the most commonly used (74 %), with left ventricular output and fractional shortening the two most common measurements made. The majority (85 %) used volume administration as the initial intervention. Dopamine was the inotrope most commonly used initially (80 %). If the initial inotrope therapy failed, dobutamine was the most popular second-line treatment (28 %). Delayed cord clamping was used at 51 % of the centres. CONCLUSION: The definition of hypotension in ELGANs continues to follow traditional standards. Functional echocardiography is now used to assess the circulation at many centres. Volume expansion and dopamine remain the most frequently used therapies.
Keywords: novorozenec s velmi nízkou porodní hmotností; hypotenze; průzkumy a dotazníky; novorozenec; Infant, Newborn; Surveys and Questionnaires; Health Surveys; novorozenci extrémně nezralí; Humans; zdravotnické přehledy; Hypotension; Infant; Turkey; lidé; kojenec; Infant, Very Low Birth Weight; Turecko; Infant, Extremely Premature